LOXL1 and LOXL4 are novel target genes of the Zn2+-bound form of ZEB1 and play a crucial role in the acceleration of invasive events in triple-negative breast cancer cells - Hirabayashi, Daisuke; Yamamoto, Ken-ichi; Maruyama, Akihiro; Tomonobu, Nahoko; Kinoshita, Rie; Chen, Youyi; Komalasari, Ni Luh Gede Yoni; Murata, Hitoshi; Gohara, Yuma; Jiang, Fan; Zhou, Jin; Ruma, I Made Winarsa; et al. (Frontiers in Oncology, 2023)
Background: EMT has been proposed to be a crucial early event in cancer metastasis. EMT is rigidly regulated by the action of several EMT-core transcription factors, particularly ZEB1. We previously revealed an unusual role of ZEB1 in the S100A8/A9-mediated metastasis in breast cancer cells that expressed ZEB1 at a significant level and showed that the ZEB1 was activated on the MCAM-downstream pathway upon S100A8/A9 binding. ZEB1 is well known to require Zn2+ for its activation based on the presence of several Zn-finger motifs in the transcription factor. However, how Zn2+-binding works on the pleiotropic role of ZEB1 through cancer progression has not been fully elucidated. Methods: We established the engineered cells, MDA-MB-231 MutZEB1 (MDA-MutZEB1), that stably express MutZEB1 (ΔZn). The cells were then evaluated in vitro for their invasion activities. Finally, an RNA-Seq analysis was performed to compare the gene alteration profiles of the established cells comprehensively. Results: MDA-MutZEB1 showed a significant loss of the EMT, ultimately stalling the invasion. Inclusive analysis of the transcription changes after the expression of MutZEB1 (ΔZn) in MDA-MB-231 cells revealed the significant downregulation of LOX family genes, which are known to play a critical role in cancer metastasis. We found that LOXL1 and LOXL4 remarkably enhanced cancer invasiveness among the LOX family genes with altered expression. Conclusions: These findings indicate that ZEB1 potentiates Zn2+-mediated transcription of plural EMT-relevant factors, including LOXL1 and LOXL4, whose upregulation plays a critical role in the invasive dissemination of breast cancer cells.